PELATIHAN PENDIDIKAN SADAR WISATA BAGI PENGELOLA OBJEK WISATA ALAM TIRTA SARI SOSANG SUMATRA BARAT: - - Rahmi Novalita; Sumanti Sumanti; Zahara Zahara; Ifwadi Ifwadi; M. Jamil Husen (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2021)
Tirta Sari Sonsang tourist attraction is a mainstay tourist attraction for Kanagarian Tilatang Kamang, Agam Regency, West Sumatra. This tourist attraction is a natural tourist attraction that has its own uniqueness and characteristics such as fishing grounds, recreation areas for visitors in various regions. Lack of knowledge and skills of partners towards the development and management of tourism objects that can improve the economy of the local community. The purpose of this service is to increase knowledge and skills through tourism awareness training. The method used in the implementation of the service is carried out by means of program socialization, and training in the form of tourism awareness education. The results obtained with this training can help partners improve their knowledge and skills so as to create a clean, orderly, comfortable, safe, beautiful, cool, and memorable environmental tourism object.